Determinant Factors of Synchronization of Budget Documents of Regional Income and Expenditure with Local Government Work Plans Documents in Central Lombok Government Fiscal Year 2017 - Saraswati, Chandra Rukmi; Surasni, Ni Ketut; Basuki, Prayitno (International Review of Management and Marketing, 2018)
The purpose of this study was to obtain empirical evidence and analyze the impact of budget planning, budgeting politics and organizational commitment to the budget document by document synchronization of RKPD in Central Lombok District Government for Fiscal Year 2017. The type of research is associative, this research searched the correlation between one variable with another variable. Data analysis was performed using the method of partial least square (PLS) PLS smart program of version 3.0. Research shows that the budget planning, budgeting political and organizational commitment have a positive and significant impact on the budget document with document synchronization of RKPD in Central Lombok. Keywords: Budget Planning, Budgeting Political, Organizational Commitment, Document Synchronization JEL Classification: M210